INTENSIFICATION OF HIGH-VISCOSITY OILS BY MEANS OF THERMAL IMPACT ON WELLBORE - Смоловик, Ліліана Романівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The article presents analysis of the research results of the tubing warmed with ceramic heaters for the purpose of oil temperature increase. The optimal localization, power capability, and the temperature of the heater surface for the chosen levels of depth are researched.